POLA KUMAN AEROB DAN KEPEKAAN ANTIMIKROBA PADA ULKUS KAKI DIABETIK - Kurniawan, Liong Boy; Esa, Tenri; Sennang, Nurhayana (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Diabetic foot ulcer is a common complication of diabetic disease which causes morbidity and foot amputation. One major pathogenesis is infection. Microbes which infect are varied. The use of inappropriate antimicrobials can or may cause drugs resistance. Data of microbes pattern and sensitivity test is important and may guide the clinician in giving the initial therapy. The aim of this retrospective study was to know the characteristics, microbial pattern, and the sensitivity to antimicrobial drugs of 31 diabetic foot ulcer patients who were hospitalized at Wahidin Sudirohusodo Hospital, Makassar in the period of January 2009 until June 2010. The study results showed the age mean was 54.06±12.4 years old, and the onset of diabetes mellitus was 7.62±5.77 years. The common microbes were gram negative bacteria (73.52%) including Enterobacter agglomerans, Proteus mirabilis and Klebsiella pneumonia, while the most common gram positive microbe was Streptococcus sp. Gram positive microbes were sensitive to meropenem, ceforoxim and amoxilin, while Gram negative microbes were sensitive to meropenem. Based on this study, the researchers concluded that the most common microbes which infect the feet were gram negative microbes. Gram positive microbes were still sensitive to meropenem, ceforoxim and amoxilin. Gram negative microbes were sensitive to meropenem.